Beech wood (Fagus sylvatica L.) flooring structures designed to increase the basketball bounce height - Turcas Diaconu, Olimpia-Minerva; Fotin, Adriana; Cosereanu, Camelia (Springer Science and Business Media LLC, 2019)
The present paper investigates the performance of eight different structures of beech wood (Fagus sylvatica L.) floorings designed for indoor basketball game court. Floorboard strips with the same lengths and widths and different thicknesses of 20 mm and 15 mm, respectively, were used to build the tested flooring structures. Joists and noggins with the same sizes and half lap jointed form the support construction mounted on the foundation. The same construction of sports floorings was applied to both categories of floorboard strips. Four variants of each category were tested. They were different through the material and position of the shock pads placed at the contact with the foundation. These variables were set in the experiment in order to improve the basketball bounce height. The tests were carried out according to SR EN 12235 standard. The best bounce heights were recorded for structures with floorboard strips of 20 mm thickness, provided with wooden shock pads placed at the half distance between the joists and noggins joints. For thinner floorboard strips, the rubber shock pads proved to be more efficient when positioned under the half-lap joints.